The relationship of jail population to operating costs in southern county jails - Baumann, W. N. (American journal of criminal justice, 1979)
The cost of providing correctional services has been soaring in recent years, reaching a figure of $72.9 million for counties in eight southern states in 1974. Prisoner populations in these county jails ranged from one to 653. Such large outlays by small and often poorly financed governmental bodies combined with the apparent variations in jail size suggest that evidence concerning the relationship between scale of operation and average variable cost might be of significant value to local decision-makers. This paper begins with a review of previous work related to economies of scale in the public sector to provide a basis for understanding the costs associated with local jails. It proceeds to the development of a theory of the factors which affect operating costs in southern county jails—including scale of operation. These factors are then incorporated in a multiple-regression model of average variable cost. The findings indicate that approximately 90 percent of the variation in operating cost per prisoner is explained by the several independent variables of which wages, security and technology are statistically significant. Since jail size has no significant effect on operating cost per prisoner, a horizontal average variable cost curve is implied and no net economies of scale are revealed.